INCREASING THE ACTIVITY OF WOMEN'S ENTREPRENEURSHIP IN UZBEKISTAN - Aliyeva Gozzal Aliyevna (European Science Publishing, 2024)
In the article, the essence of women's entrepreneurship, its social conditions, insufficient financial literacy of women's entrepreneurship and difficulties in securing funds for activities are the most serious problems affecting activities, and to solve them it is necessary to establish contact with experienced women. entrepreneurs and those developing them researched and presented findings.
Keywords: Women's entrepreneurship. GDP, gender, microfirm, risk, strategy, female entrepreneur, corporation, joint-stock company, socio-economic.